Method for preparing flexible substrate organic thin film solar cell by adopting thin film induction active layer orientation method - ZHOU WEIHUA; LI FAN; ZENG RONG; CHEN YIWANG; SHEN LIE (2012)
The invention discloses a method for preparing a flexible substrate organic thin film solar cell by adopting a thin film induction active layer orientation method. All layers of a solar cell are prepared by adopting a roll-to-roll method. The method is characterized in that an organic thin film solar cell active layer material is rolled by adopting a metal roller of which the surface is cladded iwth a polyimide film with good orientation, thus liquid-crystal-induced orientation of an active layer is realized. According to the method for preparing the flexible substrate organic thin film solar cell by adopting the thin film induction active layer orientation method, the arrangement order of a polymer chain segment is improved, thus dispersibility and crystallinity of an electron donor material and an electron receptor material in the active layer material are improved, and the active layer with a highly-order microstructure is obtained.